FACTORS OF THE DEVELOPMENT OF EDUCATIONAL TECHNOLOGY AND MEDIA LITERACY IN A PANDEMIC SITUATION - Rafid, Muh; Ismail; Basir (EDUCATUM: Scientific Journal of Education, 2023)
This study is a form of review study related to the implementation of the use of educational technology, where this technology refers to changes and developments in society. These changes and developments make Indonesian culture also participate in these changes. Moreover, this technology refers to the overall prospect of development by describing certain parts. Like, the field of education that allocates the use of this technology as one type of field that is influenced in addition to economic, cultural or other industrial elements. Especially at the time of the ongoing pandemic like today, which asks the community to be more vigilant and even the government ordered to carry out a distance guarding process. This then gets one element of support from the ministry of education to use technology as an intermediary. Therefore, the main purpose of this study is to find out the form of influence given from the use of educational technology and literacy media in pandemic situations as well as the factors that cause this development. The method used in this study is a form of literature study method by applying elements of qualitative methods from various journals. The results of the study show some of the major influences that occur due to globalization on human resources which refer to several results, namely; (1) Government Regulation as one of the main factors in the development of this element; (2) The efficient use of educational technology in learning so that students are more familiar with audio and visual-based learning. Not just face-to-face as usual which does not provide appropriate methods in other ways that can increase students' knowledge.